Common price and volatility jumps in noisy high-frequency data - Markus Bibinger; Lars Winkelmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
We introduce a statistical test for simultaneous jumps in the price of a financial asset and its volatility process. The proposed test is based on high-frequency tick-data and is robust to market microstructure frictions. To localize volatility jumps, we design and analyze a nonparametric spectral estimator of the spot volatility process. A simulation study and an empirical example with NASDAQ order book data demonstrate the practicability of the proposed methods and highlight the important role played by price volatility co-jumps.
Keywords: E58; C14; 330; high-frequency data; microstructure noise; nonparametric volatility estimation; volatility jumps